Conflict of Interest Provisions in State Laws Governing Medical and Adult Use Cannabis. - Bowling, Candice M.; Glantz, Stanton A. (American Journal of Public Health, 2019)
Although the acceleration of cannabis legalization in the United States has spurred innovations in public administration and policymaking, there have been news accounts of public employees engaged in cannabis licensure or enforcement that constitute conflicts of interest (COIs). After conducting 3 surveys in 50 states (including Washington, DC as a state), we found that COI provisions pertaining to cannabis-related public employment fell into 2 categories: subject matter general and cannabis specific. Only 20% (6/30) of the states that legalized medical cannabis had COI provisions in their medical cannabis codes, whereas the remaining 80% rely on subject matter general provisions relating to all areas of regulated subject matter, highlighting the need for thoughtful creation of COI rules in future policymaking. By contrast, 88% (7/8) of states that have legalized adult use cannabis put their COI provisions directly in their cannabis codes or regulations. Governments should enact cannabis-specific COI policies applicable to broadly defined categories of public employees that are responsive to the unique context of bringing cannabis from the black market into the regulated market.